ANALISIS PENGALAMAN BERBELANJA GUNA MENINGKATKAN MINAT BELI PADA MARKETPLACE SHOPEE - Ratna Ratna; Herry Nurdin (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract Marketplace is an internet-based (web-based) online media where business activities and transactions between buyers and sellers are carried out. With the growing development of consumers shopping online, researchers are interested in conducting research on the shopping experience with the buying interest of STIE Bima students at the Shopee Marketplace. This study aims to determine whether the shopping experience can increase the buying interest in the Shopee Marketplace for STIE Bima Students. This research method uses quantitative research methods. The population in this study were students of STIE Bima. The number of samples of 100 respondents was selected by purposive sampling technique. The data collection technique used was a questionnaire with a Likert scale. The data analysis technique used is the validity and reliability test, regression test and T-test. The results of the analysis show that: the shopping experience can increase the buying interest of STIE Bima students at the Shopee Marketplace. This means that the better the online shopping experience Shopee customers get, who in this study are STIE Bima students, the higher the buying interest of STIE Bima Students at the Shopee Marketplace.